A linguagem onírica no teatro mítico de Nelson Rodrigues: considerações sobre o tempo e o espaço - Araújo, Meury Gardênia Lima de (2020)
The investigative thread of this work leads us to the writer Nelson Rodrigues and his dramaturgy classified as mythical, specifically the plays Anjo Negro and Senhora dos Afogados, following the methodological line that the artist pre-exists the psychoanalyst. Thus, we resorted to what Freud appointed as Darstellen (figuration) and Vorstellung (representation) to investigate Rodrigues’s language used in his scenic projection. Composing, therefore, an analogy with the oneiric processes, taking into account the Lacanian proposition that the theater presents the discourse of the Other. In this work, it is presented the playwright’s biography and the criticism about his writings to “hear” the central aspects about his stylistic that indicate to the primary processes outlined in the book The Interpretation of Dreams, by Freud, namely: displacement and condensation. Then, we proceed with the literature review to discuss about the links between Psychoanalysis and Theater from Aristotelian Catharsis, locating the paths of Lacanian Aesthetics and understanding through Freud the unconscious as “Another scene”, assimilating that body and dreams carry a writing style. Finally, we analyzed in the chosen works excerpts that point out to a lack of bounds, of edges, between the psyche and the external world. Thereby, we analyze the Rodriguean space as a form of expression of the individual’s relation in the world scene, concretizing, in the manner of the oneiric elaboration, desires and symptoms that encode a discourse of the Other in the way as it is organized the separation or alienation of the individual from the loss of the object – das Ding. In Anjo Negro, the walls widen as the loneliness of the residents increases and the mansion seems to be the protagonist’s quest for returning to the maternal womb in the mythical completeness of the past; while in Virgínia we perceive a nonlinear time, with passages that establishes a past from her associations, making her to reframe the cause of her desire as linked to childhood experiences. In Senhora dos Afogados, D. Eduarda dies missing her own hands; however, in a metonymic process that eventually made her daughter Moema disappear, who sought to merge with her mother in the eagerness to occupy her symbolic place in the family. In this play, the sea is taken as the one that borders psychic and somatic. On this, we understand the Rodriguean drama as a possibility to update affections, operating in the oneiric modes. So, we conclude that in such writing the space has a language effect.